INSTITUTIONALIZATION OF UKRAINIAN MIGRANTS’ ACTIVISM IN THE EUROPEAN UNION - Марусик, Ю. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
Different approaches to defining and evaluating the institutionalization of civic activism are considered. The data of original researches in which the author and colleagues conducted a survey of civically active Ukrainian youth in the EU countries were analyzed (in-depth interviews were used). Ukrainian youth activists operating in Germany, France, Italy, Spain, Portugal, Poland and the Czech Republic were the respondents. Based on this study, the current state of institutionalization of Ukrainian activism in various EU countries is analyzed. It has been found that the work of migrant associations is diverse and is usually based on the enthusiasm or interest of activists, which leads to flexibility, proximity to the needs and beliefs of the communities concerned, but does not guarantee a high level of sustainability. Also, the data obtained indicates the formal recognition at the state level of the relevant organizations, which means compliance with a number of requirements of the authorities of the host country. Interaction with the state institutions and local self-government of both host country and Ukraine in the course of project activities is typical, which shows another aspect of the process of institutionalization of Ukrainian migrants’ activism. An important feature of activism is the «mobilization» approach, which is characterized by the activities of small organizations that unite a wider circle of less active supporters and mobilizes them at certain times. It is revealed that the current state of institutionalization of Ukrainian activism in the EU indicates both positive features (flexibility and compliance with the requests of communities or individuals in need of assistance; taking into account the current situation in Ukraine) and negative (dependence on the initiative of individual activists, relative unpredictability of activities as well as results).